Diversity of indigenous arbuscular mycorrhizal fungi in rhizosphere of upland rice (Oryza sativa L.) varieties in Southwest Nigeria - Olubode, Adebanke A (Acta fytotechnica et zootechnica, 2020)
Arbuscular mycorrhizal fungi (AMF) have the potential to increase crop productivity and play a key role in the functioning and sustainability of most agroecosystems. However, limited information is available on the divervisity of AMF associated with upland rice varieties in Southwest Nigeria. Field survey was conducted to investigate colonization and diversity of AMF in 13 upland rice varieties commonly grown in Southwest Nigeria. Root and soil samples were collected from rice fields in 2012. The results showed natural root colonization of all the rice varieties by AMF with highest root colonization in ITA 157and Ofada. The spore densities retrieved from the different rhizospheres were relatively high, varying from 13 spores in UORW 111 to 174 spores in Ofada with a mean of 67.6 spores per 20 g dry soil. Glomus was observed to be the most abundant AMF genus. Funneliformis mosseae was the most frequently occurring AMF species (96.2%) with relative density (RD) of 32.2%, followed by Glomus intraradices, Claroideoglomus etunicatum, and Glomus clareium. This study showed that AMF naturally colonized the roots of these rice varieties and diversity of different AMF genera in rice rhizosphere. This study will help draw attention to natural colonization of AMF in rice producing areas of Nigeria that can influence future possibility of using inocula of the dominant AMF species in upland rice cultivation.